Pendampingan Santri TPQ Baiturrahman Palangka Raya Mengenai Adab Dan Doa Harian - Ramadhan Wirayudha; M. Rifani Al-Ghazali; Abdullah Abdullah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Islamic Religious Education has a central role central role in creating religiously observant Indonesians. Taman Pendidikan Al-Qur'an (TPQ) plays an important role in shaping children's character through teaching reading the Qur'an, prayer practice, memorization of short letters, and daily prayers. daily prayers. TPQ Baiturrahman in Palangka Raya is an institution that teaching Islamic manners and daily prayers to its students. This assistance is carried out by ustadz and ustadzah to shape a person who is religiously observant, responsible, and caring for others. The teaching methods used are memorization and lectures, with a test of memorization of daily prayers as an evaluation. This learning aims to to produce students who are able to memorize daily prayers, understand the adab when in a place of worship, and have a qualified understanding of religion. However, there are still students who have difficulty in memorizing daily prayers, due to factors such as their memory power. daily prayers, caused by factors such as less strong memorization power and the learning process. learning process